Servitization dan Firm Performance Pada Usaha Bengkel: Risk-Taking sebagai Pemediasi - Tanjung, Vero; Masdupi, Erni (Jurnal Informatika Ekonomi Bisnis, 2025)
The rapid increase in private vehicle use has also boosted the growth prospects of repair shops in Indonesia. In this context, service plays a crucial role in creating new revenue streams for businesses while contributing to improved company performance. However, risk-taking is crucial in bridging the gap between the concept and implementation of this strategy. This study aims to identify the influence of service on company performance in repair shops in West Sumatra, with risk-taking as a mediating variable. Using quantitative methods, this study collected data from 80 repair shops in West Sumatra and analyzed it using a Structural Equation Modeling-Partial Least Squares (SEM-PLS) approach. The results show a positive and significant relationship between servitization and risk-taking, as well as between risk-taking and company performance. Furthermore, servitization has also been shown to have a positive and significant effect on company performance. Further findings indicate that risk-taking mediates the positive and significant relationship between servitization and company performance. Thus, this study confirms that servitization and risk-taking play a significant role in improving company performance. This research contributes to the broader understanding of business models, particularly in the repair shop sector, where the concept of service is generally studied more in the context of manufacturing companies. This research highlights how servitization can shape firm performance through its mediating role in risk-taking.